Influence of contact electrode and light power on the efficiency of tandem perovskite solar cell: Numerical simulation. (15th September 2021) - Farhadi, Bita; Ciprian, Matteo; Zabihi, Fatemeh; Liu, Aimin
Highlights: The effect of MAPbI3 and MASnI3 as a light-absorbing layer is elucidated. The effects of ETL and HTL layer materials are calculated and compared. The effects of contact, defects, light radiation power, light direction are compared. The temperature effects on the PSC is investigated. Maximum optimization efficiency can reach 30.88%. Abstract: This paper presents our theoretical study of tandem perovskite solar cells, simulated using a solar cell capacitance one-dimensional tool. The simulation reveals that the efficiency reaches 30.88% while combining Methylammonium Lead Iodide (MAPbI3 ) and Methylammonium Tin Iodide (MASnI3 ) as an absorber. The present work has also analyzed the effects of different materials as an Electron Transport Layer and Hole Transport Layer, and the effects of back metal contact, absorber layers defects, light radiation power, light direction, etc. Molecular Dynamic study has found that the thermal properties of MAPbI3 and MASnI3 perovskite layers are favorable to the solar cell efficiency and performance. In addition, the effect of temperature variation on solar cell performance is investigated, and the impact of defect density of the absorber layer is also explored. It was found that low defect density is helpful to achieve high device performance. Moreover, the work function of the front metal contact plays an important role, and it should be more than 5.31 eV for the proposed devices to achieve high performance.